2022
DOI: 10.21608/mjapam.2022.247518
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant Toxicity of Some Plant Volatile Oils Against Stored Grain Weevils

Abstract: Cereal grains considered one of the most important crops in Egypt and all over the world, these stored grains are infested with many insects that reduce their economic value and cause a significant problem for food security. The current study aimed to protect stored grains from infestation of different weevil species using plant oils as fumigants. Six plant volatile oils i.e., Garlic, Clove, Peppermint, Orange, Onion, and Camphor were used to determine the fumigant toxicity of oils the adults of Sitophilus gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Regarding the protein content of the two samples, there was a decrease in protein during all the storage periods, while the untreated sample recorded the highest decrease (24.98 %) compared to the treated sample (25.82) %. The findings align with those of Abd El-Raheem et al (2022), which reported that stored grains (rice, corn, and wheat) had decreases in total protein due to insect infestation during storage than grains treated with certain essential oils (garlic, clove, peppermint, orange, onion, and camphor). This reduction in protein content of untreated cowpea sample during storage may be due to insect infestation.…”
Section: Moisture Protein and In Vitro Protein Digestibility Of Treat...supporting
confidence: 89%
“…Regarding the protein content of the two samples, there was a decrease in protein during all the storage periods, while the untreated sample recorded the highest decrease (24.98 %) compared to the treated sample (25.82) %. The findings align with those of Abd El-Raheem et al (2022), which reported that stored grains (rice, corn, and wheat) had decreases in total protein due to insect infestation during storage than grains treated with certain essential oils (garlic, clove, peppermint, orange, onion, and camphor). This reduction in protein content of untreated cowpea sample during storage may be due to insect infestation.…”
Section: Moisture Protein and In Vitro Protein Digestibility Of Treat...supporting
confidence: 89%